2019
DOI: 10.7554/elife.47301
|View full text |Cite
|
Sign up to set email alerts
|

Comment on 'Single nucleus sequencing reveals evidence of inter-nucleus recombination in arbuscular mycorrhizal fungi'

Abstract: Chen et al. recently reported evidence for inter-nucleus recombination in arbuscular mycorrhizal fungi (Chen et al., 2018a). Here, we report a reanalysis of their data. After filtering the data by excluding heterozygous sites in haploid nuclei, duplicated regions of the genome, and low-coverage depths base calls, we find the evidence for recombination to be very sparse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…The discovery of inter-nuclear recombination in AMF was, however, challenged. Specifically, it was suggested that recombination events in AMF drop significantly once heterozygous, duplicated regions covering SNPs and sites supported by less than five reads are removed from available datasets from single nuclei (Auxier and Bazzicalupo, 2019). Here, we show that the removal of duplicates, heterozygous positions and sites supported by less than five reads still retrieves significant inter-nuclear recombination within available datasets (Chen et al, 2018b).…”
Section: Introductionmentioning
confidence: 59%
See 4 more Smart Citations
“…The discovery of inter-nuclear recombination in AMF was, however, challenged. Specifically, it was suggested that recombination events in AMF drop significantly once heterozygous, duplicated regions covering SNPs and sites supported by less than five reads are removed from available datasets from single nuclei (Auxier and Bazzicalupo, 2019). Here, we show that the removal of duplicates, heterozygous positions and sites supported by less than five reads still retrieves significant inter-nuclear recombination within available datasets (Chen et al, 2018b).…”
Section: Introductionmentioning
confidence: 59%
“…To this end, plans are underway to sequence individual AMF nuclei using long-read sequencing technologies, and perform single nuclei genotyping using complete, phased genome references for all dikaryotic AMF isolates. Long-read sequencing will be important to reveal the exact origin of the heterozygous sites in single nuclei datasets – i.e., whether some of these represent miss-mapped reads, sequence errors, aneuploidy or contaminants - as these are often found along recombination tracts (see paper and Auxier and Bazzicalupo, 2019 ). Lastly, producing a recombining progeny by crossing compatible homokaryotic AMF isolates will be key to conclusively demonstrate how/when sexual reproduction (meiosis) occurs in AMF.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations